Mechanisms and functions of extracellular vesicle release in vivo—What we can learn from flies and worms. Issue 2 (4th March 2017) - Beer, Katharina B.; Wehman, Ann Marie
ABSTRACT: Cells from bacteria to man release extracellular vesicles (EVs) that contain signaling molecules like proteins, lipids, and nucleic acids. The content, formation, and signaling roles of these conserved vesicles are diverse, but the physiological relevance of EV signaling in vivo is still debated. Studies in classical genetic model organisms like C. elegans and Drosophila have begun to reveal the developmental and behavioral roles for EVs. In this review, we discuss the emerging evidence for the in vivo signaling roles of EVs. Significant effort has also been made to understand the mechanisms behind the formation and release of EVs, specifically of exosomes derived from exocytosis of multivesicular bodies and of microvesicles derived from plasma membrane budding called ectocytosis. In this review, we detail the impact of flies and worms on understanding the proteins and lipids involved in EV biogenesis and highlight the open questions in the field.